2010
DOI: 10.1111/j.1365-3083.2010.02382.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Ovalbumin and Ovalbumin Peptide 323-339 Responses in Allergic Mice: Humoral and Cellular Aspects

Abstract: Ovalbumin (OVA) is widely used in allergy research. OVA peptide 323‐339 has been reported to be responsible for 25–35% of isolated BALB/c mouse T‐cell response to intact OVA. An investigation of whether OVA and OVA 323‐339 molecules can induce equivalent in vivo and in vitro immune responses was conducted. Eight‐week‐old BALB/c mice were randomly divided into three groups: OVA, OVA 323‐339 and saline. On days 0, 7, 14, mice were intraperitoneally injected with 25 μg OVA or OVA 323‐339 absorbed on 300 μg Alum, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…It also has been shown by research IgE levels in mice exposed ovalbumin. [2][3][4][5] Problems that arise and has not been solved to date is not yet found a cure for allergies with effect minimum side. Therefore, it needs proper handling solutions allergies, with therapies that have minimal side effects.…”
Section: Introductionmentioning
confidence: 99%
“…It also has been shown by research IgE levels in mice exposed ovalbumin. [2][3][4][5] Problems that arise and has not been solved to date is not yet found a cure for allergies with effect minimum side. Therefore, it needs proper handling solutions allergies, with therapies that have minimal side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Here, recombinant OVA O-mannosylation has been shown to be effective in MR targeting [190]. However, in a previous study, the OVA323-339 epitope produced a Th1 response in mice but its immunogenicity was limited compared to the full OVA protein [189] confirming the need for an adjuvant system for small proteins or peptide epitopes as vaccine candidates.…”
Section: Introductionmentioning
confidence: 93%
“…indicated that in allergenic mice, the OVA323-339 epitope (using 300 µg alum as adjuvant) produced a Th1 response but its immunogenicity was limited compared to the full native OVA protein [189].…”
Section: Model Antigen Selectionmentioning
confidence: 99%
See 2 more Smart Citations